2017
DOI: 10.1002/pros.23344
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Heritability of Prostate Cancer‐Specific Survival Using Population‐Based Registers

Abstract: Heritability of prostate cancer-specific survival is considerably lower than for prostate cancer incidence. This supports a hypothesis that susceptibility of disease and progression of disease are separate mechanisms that involve different genes. Further assessment of the genetic basis of prostate cancer-specific survival is warranted. Prostate 77:900-907, 2017. © 2017 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…6 So far, genome-wide studies have identified more than 100 common mutations in prostate cancer patients, which account for a significant portion of the genetic factors underlying prostate cancer, including mutations in DNA damage repair genes. [7][8][9][10] Genomic DNA is frequently harmed by a variety of internal and external factors such as double-strand breaks. Cells have evolved a well-coordinated signal cascade network called DNA damage response (DDR) to maintain genomic integrity, which senses and transmits damage signals to effector proteins and induces cell responses such as cell cycle arrest, DNA repair pathway activation, and cell death, and many genes are involved, including BRCA, ATM, and CHEK2.…”
Section: Introductionmentioning
confidence: 99%
“…6 So far, genome-wide studies have identified more than 100 common mutations in prostate cancer patients, which account for a significant portion of the genetic factors underlying prostate cancer, including mutations in DNA damage repair genes. [7][8][9][10] Genomic DNA is frequently harmed by a variety of internal and external factors such as double-strand breaks. Cells have evolved a well-coordinated signal cascade network called DNA damage response (DDR) to maintain genomic integrity, which senses and transmits damage signals to effector proteins and induces cell responses such as cell cycle arrest, DNA repair pathway activation, and cell death, and many genes are involved, including BRCA, ATM, and CHEK2.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, our method can be straightforwardly applied to variable selection in multicomponent AFT models with various random‐effect structures (nested and/or crossed) and also in the AFT models with left truncated and right censored . The structure equation models (SEMs) allow for good modeling of log‐normal AFTs (eg, the work of Szulkin et al). Extension to the SEM via the proposed method would be an interesting future topic.…”
Section: Discussionmentioning
confidence: 99%
“…However, these SNPs (single nucleotide polymorphism) mostly show little or no ability to discriminate between indolent and fatal forms of the disease. In contrast to the high genetic component accounting for the overall prostate cancer risk, the heritability of prostate cancer-specific survival was estimated to be 10% ( 5 ) and consequently, few genetic variants have been specifically associated with aggressive prostate cancer ( 6 , 7 ). Since the majority of all diagnosed prostate cancer cases do not progress to lethality, biological markers that can distinguish between potentially lethal and non-aggressive cases would greatly improve prognostication and guide treatment decisions.…”
Section: Introductionmentioning
confidence: 99%